Phytoplankton and Epipelon Responses to Clear and Turbid Phases in a Seepage Lake (Buenos Aires, Argentina) - Casco, Maria Adela (2009)
Annual changes in the algal density and concentrations of chlorophyll a, total phosphorus, and organic matter were analyzed in water and sediments at four sites characterized by the presence or absence of submerged and emergent macrophytes, during turbid- and clear-water conditions to determine the contribution of the algal components of the plankton and the epipelon and to identify the most typical species in each community. Three states were recognized: one turbid and two clear, with different submerged macrophyte cover. The peaks of phytoplankton and epipelon occurred in the turbid phase, whereas the highest proportion of true epipelic algae in sediments was reached in the second clear phase. The Oscillatoriaceae dominated during the turbid phase in the water and throughout the entire year within the sediments.